Protocol for a pharmacogenetic study of antidepressants: characterization of drug-metabolizing profiles of cytochromes CYP2D6 and CYP2C19 in a Sardinian population of patients with major depressive disorder. (October 2021) - Pinna, Marco; Manchia, Mirko; Pisanu, Claudia; Pinna, Federica; Paribello, Pasquale; Carta, Andrea; Meloni, Anna; Conversano, Claudio; Del Zompo, Maria; Mola, Francesco; Squassina, Alessio; Carpiniello, Bernardo
Abstract : The effectiveness of antidepressants shows high interindividual variability ranging from full symptomatologic remission to treatment-resistant depression. Many factors can determine the variation in the clinical response, but a fundamental role is played by genetic variation within the genes encoding for the enzymes most involved in the metabolism of antidepressant drugs: the CYP2D6 and CYP2C19 isoforms of the cytochrome P450 system. This study is poised to clarify whether the different metabolizing phenotypes related to CYP2D6 and CYP2C19 could have an impact on the clinical efficacy of antidepressants and whether the frequency of these phenotypes of metabolization shows differences in the population of Sardinian patients compared to other Caucasian populations. The sample is being recruited from patients followed-up and treated at the Psychiatric Unit of the Department of Medical Science and Public Health, University of Cagliari and the University Hospital Agency of Cagliari (Italy). The study design includes three approaches: (1) a pharmacogenetic analysis of 80 patients diagnosed with MDD resistant to antidepressant treatment compared to 80 clinically responsive or remitted patients; (2) a prospective arm ( N  = 30) of the study where we will test the impact of genetic variation within the CYP2D6 and CYP2C19 genes on clinical response to antidepressants and on their serum levels and (3) the assessment of the socio-economic impact of antidepressant therapies, and estimation of the cost-effectiveness of the pharmacogenetic test based on CYP genes.